Analisis Perhitungan Penerapan Aditif SG dalam Job Mix Formula terhadap Efisiensi dan Konsistensi Mutu Beton - Dea Indriani; Deny Ernawan; Adi Subandi; Endang Setiadi Permana (Jurnal Kendali Teknik dan Sains, 2025)
Consistent and efficient concrete quality in each implementation is one of the main factors in the success of construction projects. Concrete as a structural material requires strict quality control in order to meet the technical standards that have been set. One way to improve the quality of concrete is to add certain additives to the job mix formula (JMF). This research is focused on the application of SG type additives known as chemical-based additives to improve the properties of fresh concrete and hard concrete. SG additives have an important function in increasing workability, speeding up or slowing down the binding time as needed, maintaining quality stability, and strengthening concrete finishes. In this study, a comparison was made between a concrete mixture with SG additives and a concrete mixture without additives. The tests included slump parameters, initial binding time, and compressive strength at 7 and 28 days of age. The test results showed a significant difference, especially in the improvement of the consistency and compressive strength of concrete with the use of additives. The results of the discussion showed a comparison of Trial Mix 1 and Trial Mix 2 that are different in terms of material composition, cost efficiency, and compressive strength of concrete. Trial Mix 2 with the composition of cement, admixture, water, and aggregate (sand and split) showed more optimal results. The compressive strength achieved was 821,396.00 kg/cm² at the age of 28 days. In terms of cost, Trial Mix 2 requires Rp. 351,582.00 per m³, with an efficiency difference of around Rp. 32,953.00 per m³ compared to the previous mix